Where Do Sounds Fit Within Informal Logic? - Groarke, Leo (Informal Logic, 2018)
In response to commentaries by Eckstein and Kišiček, I argue that the study of auditory arguments is very much in keeping with the critical thinking (and epistemological) ideals that motivate informal logic. In the process I support further research on sound figures and the meaning of sound (and a possible “auditory dictionary”) that would enhance our ability to analyze auditory arguments.